Adsorption performance and mechanism of Li+ from brines using lithium/aluminum layered double hydroxides-SiO2 bauxite composite adsorbents - Qian, Cheng; Zheng, Mianping; Zhang, Yongsheng; Xing, Enyuan; Gui, Baoling (Frontiers in Chemistry, 2023)
A combined method of solid-phase alkali activation and surface precipitation was used to prepare the lithium/aluminum layered double hydroxides-SiO 2 loaded bauxite (LDH-Si-BX) and applied to adsorb Li + in brines. In the study, various of characterization techniques such as SEM, XRD, BET, Zeta potential and XPS were applied to characterize and analyze the adsorbents. The adsorption-desorption performance of LDH-Si-BX for Li + in brines were systematically investigated, including adsorption temperature, adsorption time, Li + concentration and regeneration properties. The results indicated that the adsorption kinetics were better fitted by pseudo-second-order model, Langmuir model could match the adsorption isotherm data and the maximum Li + capacity of 1.70 mg/g at 298K. In addition, in the presence of coexisting ions (Na + ,K + ,Ca 2+ ,Mg 2+ ), LDH-Si-BX showed good selective adsorption of Li + , and the pH studies demonstrated that the adsorbents had better Li + adsorption capacity in neutral environments. In the adsorption process of real brines, LDH-Si-BX had a relatively stable adsorption capacity, after 10 cycles of adsorption and regeneration, the adsorption capacity decreased by 16.8%. It could be seen that the LDH-Si-BX adsorbents prepared in this report has the potential of Li + adsorption in brines.